New directions for retranslation research: Lessons learned from the archaeology of retranslations in the Finnish literary system - Koskinen Kaisa; Paloposki Outi (Brazil, 2022)
In this article, we discuss the archaeological phase of our research into retranslating in the Finnish literary system. We address the issue from the point of view of the past and future development on retranslation research, focusing on methodology. We argue that for our understanding of the phenomenon to advance, the traditional case study orientation of retranslation research needs to be complemented with other, macro level approaches. We discuss what kinds of research questions our archaeological data allowed us to generate, how collecting bibliographical information of a larger set of translations allowed us to place individual case studies within the bigger picture, and how it allowed us to compare our findings to similar, macro level research done by other scholars. The next step for retranslation research will, we believe, consist of studies asking new questions on the basis of such macro level empirical evidence (tested on new, targeted data sets or case studies) and comparisons between these studies completed in different cultural, historical and literary contexts.